Pengaruh Penambahan Limbah Serbuk Kaca dan Kapur Padam pada Pembuatan Genteng Beton Ramah Lingkungan - Dzikriya Ahmad Arkhanditya; Rivaldi Sigalingging; H Hartono; Bambang Setiabudi (Jurnal Sipil dan Arsitektur, 2024)
In Indonesia, concrete roof tiles are still relatively expensive. This can be seen from the composition of the mixture and the concrete tile production process. Based on cost considerations, the alternative is to use glass powder waste and quenched lime. Lime as an alternative choice because the chemical elements contained are almost the same as cement. Glass powder waste contains silica which is expected to increase the density of concrete roof tiles. Therefore, this research was conducted with the aim to see the effect of adding glass powder waste and slaked lime to the values of flexural load, absorption, and water seepage. The method used is the experimental method, with a mixture of cement and sand composition, namely 1: 3 and using 4 variations of the test object, namely for quenched lime with variation A 0%; B 10%; C 0%; D is 10% by weight of cement while for variations of glass powder A is 0%; B 0%; C 10%; D 10% by weight of sand. This test includes appearance, size, value of bending load, absorption, and water seepage. The result of average bending load in variations A = 1548,51 N, B = 1562,25 N, C = 1675,57 N, D = 1751,43 N. For the result of average water absorption in variations A = 9,248%, B = 6,675%, C = 9,512%, D = 7,093%. The use of glass powder waste and extinguished lime can increase the value of bending load, absorption and water seepage compared to ordinary concrete roof tiles. So as to produce concrete roof tiles that are economical and also reduce waste but still meet the quality according to SNI.